2017
DOI: 10.15277/bjd.2017.139
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetes and dementia

Abstract: Continued advances in medicine have contributed to an ageing population in most countries, with a resultant increased prevalence of dementia as well as type 2 diabetes. Consequently, the combined co-morbidity of diabetes and dementia is on the increase. While there is a wealth of therapeutic options for diabetes in general, we need to adapt these medications and strategies to suit those with dementia. The intricacies of managing diabetes in patients with cognitive dysfunction are multiple and require a sound u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Cognitive decline may worsen self-management of T2D therapy, even in early and undetected stages of dementia. This is a vulnerable phase, as cognitive changes may be aggravated by incorrect self-management of T2D as a consequence of hypo- or hyperglycaemia [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive decline may worsen self-management of T2D therapy, even in early and undetected stages of dementia. This is a vulnerable phase, as cognitive changes may be aggravated by incorrect self-management of T2D as a consequence of hypo- or hyperglycaemia [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising, as diabetes is largely a self-managed disease that necessitates high-level cognitive capabilities for patients to properly adhere to medication and lifestyle regimens. However, memory loss, impaired problem-solving, and other ADRD symptoms make diabetes management extremely difficult for people living with ADRD and their family caregivers [ 14 , 60 ]. Previous recommendations and studies have suggested that for people with cognitive impairment, diabetes care should be individualized and patient-centered [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous recommendations and studies have suggested that for people with cognitive impairment, diabetes care should be individualized and patient-centered [ 60 ]. The glycemic target (eg, hemoglobin A 1c , fasting glucose, and postprandial glucose) should also be relaxed [ 14 ]. However, the incorporation of these recommendations into daily care regimens has rarely been studied in individuals living with ADRD and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread distribution of GLP-1 receptors in gastrointestinal tract, brain and bone extends their role beyond their use as anti-diabetic agents to far greater potentials. Indeed, improvement of cognitive function by liraglutide, via its effects on glucose and lipid metabolism, both directly and through an increase in osteocalcin, suggests that the drug might may have the benefit of reducing cognitive impairment that is commonly associated with diabetes [54,55].…”
mentioning
confidence: 99%